Food packaging bag and preparation method thereof
By using polylactic acid, polybutylene 2,5-furandicarboxylate, POSS-based capacity-enhancing components and modified zero-valent nano-ferrous, the problem that food packaging bags are difficult to have both environmentally friendly and high barrier properties is solved, and the problem of food packaging bags is realized. Improved biodegradation, mechanical properties and fresh preservation effect.
Patent Information
- Application Number
- CN202411287158.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Existing food packaging bags are difficult to have both environmentally friendly and high barrier properties. Petroleum-based high barrier plastic packaging bags are not degradable, and the barrier properties of biodegradable materials are insufficient.
Polylactic acid, polybutylene 2,5-furandicarboxylate, POSS-based compatibilizing components and modified zero-valent nanoferric as raw materials were used to prepare POSS-based compatibilizing components through ene-click reaction and functional group conversion method. Food packaging bags with high barrier and mechanical properties are prepared by combining casting method.
The biodegradability, mechanical properties and fresh preservation effect of food packaging bags have been improved. The POSS-based capacity-enhancing components have improved the adhesion and oxygen resistance of the material, and the modified zero-valent nano-ferrous iron has improved the dispersion and oxygen resistance of the .
Smart Images

Figure BDA0005043416770000091 
Figure BDA0005043416770000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging bags, and in particular relates to a food packaging bag and a preparation method thereof. Background Art
[0002] With the acceleration of modern life and the rise of the takeaway industry, the market demand for food packaging bags, as a film container that directly contacts food and is used to hold and protect food, is growing. Food packaging bags are not only required to have basic preservation and storage functions, but also gradually put forward higher requirements in terms of environmental protection and mechanical properties.
[0003] In the prior art, the materials used to prepare food packaging bags are diverse, but there are some common problems. For example, petroleum-based high-barrier plastic packaging bags have good barrier properties and processability, and are low in cost, but they do not have degradable properties. In addition, petroleum is a non-renewable and limited resource, resulting in a low recycling rate of plastics, which leads to environmental pollution and depletion of petroleum resources. Biodegradable materials are green and environmentally friendly materials, such as polylactic acid (PLA) materials, but compared with polyethylene terephthalate (PET) materials, the water vapor and oxygen permeability coefficients of PLA are one order of magnitude higher, and the barrier properties are poor, resulting in limited application in food packaging materials.
[0004] Therefore, providing an environmentally friendly food packaging bag with high barrier properties is a technical problem that needs to be solved at present. Summary of the invention
[0005] The object of the present invention is to provide a food packaging bag and a preparation method thereof, so as to solve the problem that the existing food packaging bags are difficult to have both environmental friendliness and high barrier properties.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A food packaging bag comprises the following raw materials in parts by weight: 28-38 parts of polylactic acid, 2-12 parts of polybutylene 2,5-furandicarboxylate, 2-5 parts of POSS-based compatibilizing components, and 0.6-1.2 parts of modified zero-valent nano-iron.
[0008] Further, the POSS-based compatibilizing component is prepared by the following steps:
[0009] Add epoxidized vinyl POSS, mercapto Schiff base, benzoin dimethyl ether and tetrahydrofuran into a flask, stir for 20-40 minutes, place under ultraviolet light to react for 30 minutes, and remove tetrahydrofuran by rotary evaporation.
[0010] Using epoxidized vinyl POSS containing epoxy and vinyl bifunctional groups and mercapto Schiff base as raw materials, the POSS-based compatibilizing component was obtained through ene-click reaction.
[0011] Furthermore, the usage ratio of epoxidized vinyl POSS, mercapto Schiff base, benzoin dimethyl ether and tetrahydrofuran is 2-2.1 g: 2.5 g: 0.02 g: 50-100 mL.
[0012] Furthermore, the power of the ultraviolet lamp is 300-600W and the wavelength is 365nm.
[0013] Further, the epoxidized vinyl POSS is prepared by the following steps:
[0014] Add chloroform to a flask, and then add octavinyl-POSS, acetic acid and concentrated sulfuric acid in sequence. Stir and heat to 60°C. Add hydrogen peroxide solution dropwise to the flask. After the addition is complete, heat to reflux and react for 18 hours. After the reaction is completed, remove the upper liquid by separation, and wash the lower liquid with sodium bicarbonate solution and deionized water for 3-5 times respectively to remove the aqueous phase. The obtained solution is evaporated in a ventilated place at room temperature for 12 hours, and then vacuum evaporated at 60°C for 12 hours.
[0015] Furthermore, the dosage ratio of chloroform, octavinyl-POSS, acetic acid, concentrated sulfuric acid and hydrogen peroxide solution is 110mL:6g:25mL:0.8mL:50mL, the mass fraction of concentrated sulfuric acid is 98%, the mass fraction of hydrogen peroxide solution is 30%, and the mass fraction of sodium bicarbonate solution is 4-8%. Octavinyl-POSS is used as a substrate to prepare epoxidized vinyl POSS by a functional group conversion method.
[0016] Further, the mercapto Schiff base is prepared by the following steps:
[0017] Add cinnamaldehyde into a flask filled with anhydrous ethanol, stir for 3-5 minutes, then add dropwise the ethanol solution of β-mercaptoethylamine at a dropping rate of 3-4 mL / min. After the addition is complete, add acetic acid, stir, and react at 55-65°C for 4 hours. After the reaction is completed, cool to room temperature, remove the anhydrous ethanol by rotary evaporation to obtain a crude product, recrystallize the crude product with anhydrous ethanol, and dry it in vacuo.
[0018] Furthermore, the molar ratio of cinnamaldehyde to β-mercaptoethylamine is 1:1, the amount of acetic acid used is 0.2-0.4 times the sum of the masses of cinnamaldehyde and β-mercaptoethylamine, and cinnamaldehyde and β-mercaptoethylamine are used as raw materials to obtain a mercapto Schiff base through the reaction between amino groups and aldehyde groups.
[0019] Further, the modified zero-valent nano-iron is prepared by the following steps:
[0020] Mix a polyethylene glycol-400 aqueous solution with a mass concentration of 1g / L and a ferrous sulfate solution with a concentration of 1mol / L. Add a potassium borohydride solution with a concentration of 2.5mol / L under a nitrogen environment while stirring. After the addition is completed, stir the reaction for 10-20min, then filter, wash the filter cake with deionized water and dry it, transfer it to anhydrous ethanol and stir it for 5-10min, filter again, wash the filter cake with anhydrous ethanol and acetone for 2-3 times respectively, and dry it again.
[0021] Nano zero-valent iron has good reducibility, but it is easy to agglomerate and has poor compatibility with the polylactic acid matrix during the application process. To this end, the present invention uses polyethylene glycol-400 to perform surface modification on the zero-valent nano-iron to obtain modified zero-valent nano-iron. On the one hand, the dispersibility of the zero-valent nano-iron in the polymer matrix is improved, and on the other hand, the toughness of the polylactic acid is improved with the help of the flexible chain of polyethylene glycol-400.
[0022] Furthermore, the volume ratio of the polyethylene glycol-400 aqueous solution, the ferrous sulfate solution and the potassium borohydride solution is 28-56:100:100.
[0023] Furthermore, 0.22 μm water-based microporous filter membrane is used for filtration.
[0024] A method for preparing a food packaging bag comprises the following steps:
[0025] Polylactic acid and poly (butylene 2,5-furandicarboxylate) were dried in an oven at 80°C for 12 hours respectively, and then added into a mixer together with a POSS-based volume-increasing component and modified zero-valent nano-iron at a speed of 50-100 r / min and stirred for 30 minutes to obtain a mixture, which was transferred to a screw extruder and melt-extruded to obtain composite pellets, which were made into food packaging films by a casting method, and then cut and processed to obtain food packaging bags.
[0026] Furthermore, the screw extruder is a twin-screw extruder, and the temperatures of the seven zones from the feed part to the head part are set to 170°C, 180°C, 190°C, 190°C, 190°C, 180°C, and 180°C, respectively. The feed rate is 150g / min and the screw speed is 60r / min.
[0027] Furthermore, the extrusion section temperature of the casting equipment is 170-230°C, the die temperature is 230°C, and the cooling roller temperature is 25-35°C.
[0028] Beneficial effects of the present invention:
[0029] 1. The present invention uses polylactic acid, poly (butylene 2,5-furandicarboxylate), POSS-based volume-increasing component and modified zero-valent nano-iron as raw materials, utilizes poly (butylene 2,5-furandicarboxylate) with high toughness and strength to blend with polylactic acid, achieves a balance between rigidity and toughness of the composite material, and introduces POSS-based volume-increasing component and modified zero-valent nano-iron to improve the barrier property and mechanical property of the composite material, so that the prepared packaging bag finally has not only good biodegradability, but also good mechanical property and excellent fresh-keeping effect.
[0030] 2. The POSS-based expanding component prepared by the present invention has a cage-like polysilsesquioxane structure, which is introduced into the packaging film base material to play the role of reinforcing the composite material, and due to the presence of the active epoxy group, the POSS-based expanding component can react with the end groups of polylactic acid and poly-2,5-butylene furandicarboxylate in situ, and the polylactic acid chain and the poly-2,5-butylene furandicarboxylate chain are grafted, thereby improving the adhesion of the two incompatible interfaces and avoiding the rupture of the film material under low stress, thereby improving the mechanical properties of the packaging bag. In addition, when the food in the packaging bag produces acidic moisture due to respiration, the Schiff base structure in the POSS-based expanding component decomposes, and cinnamaldehyde is released into the storage space, thereby playing the role of antiseptic and fresh-keeping. This fresh-keeping method not only avoids the direct contact of the preservative with the food, but also has a long action time.
[0031] 3. The present invention adds modified zero-valent nano-iron to the food packaging bag. The modified zero-valent nano-iron has good dispersibility in the polymer matrix and can play a role of heterogeneous nucleation, thereby improving the crystallization behavior of polylactic acid and improving the mechanical properties of the packaging film in combination with the presence of flexible chains. In addition, the zero-valent nano-iron can contact and react with oxygen, consume the oxygen that penetrates into the packaging film, and improve the oxygen barrier performance of the packaging film. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The sources of some raw materials in this application are as follows:
[0034] Polylactic acid: CAS number 31852-84-3, active ingredient content ≥ 99%;
[0035] Polybutylene 2,5-furandicarboxylate was purchased from Ningbo Jisu New Material Technology Co., Ltd.
[0036] Example 1
[0037] A POSS-based compatibilizing component is prepared by the following steps:
[0038] Add 2 g of epoxidized vinyl POSS, 2.5 g of mercapto Schiff base, 0.02 g of benzoin dimethyl ether and 50 mL of tetrahydrofuran into a flask, stir for 20 min, place under ultraviolet lamp (power 300 W, wavelength 365 nm) to react for 30 min, and remove tetrahydrofuran by rotary evaporation.
[0039] Epoxidized vinyl POSS is made by the following steps:
[0040] Add 110 mL of chloroform into a flask, and add 6 g of octavinyl-POSS, 25 mL of acetic acid and 0.8 mL of 98 wt % concentrated sulfuric acid in sequence, stir and heat to 60 ° C, add 50 mL of 30 wt % hydrogen peroxide solution into the flask, after the addition is complete, heat to reflux for 18 hours, after the reaction is completed, remove the upper liquid by separation, and wash the lower liquid with 4 wt % sodium bicarbonate solution and deionized water for 3 times respectively to remove the aqueous phase. The obtained solution is evaporated in a ventilated place at room temperature for 12 hours, and then vacuum evaporated at 60 ° C for 12 hours.
[0041] Mercapto Schiff bases are prepared by the following steps:
[0042] Add 0.1 mol cinnamaldehyde into a flask with 130 mL of anhydrous ethanol, stir for 3 min, then add dropwise a solution consisting of 0.1 mol β-mercaptoethylamine and 80 mL of anhydrous ethanol, and control the dropping rate to 3 mL / min. After the addition is complete, add acetic acid in an amount of 0.2 times the sum of the mass of cinnamaldehyde and β-mercaptoethylamine. Stir and react at 55 °C for 4 h. After the reaction is completed, cool to room temperature, remove anhydrous ethanol by rotary evaporation to obtain a crude product, recrystallize the crude product with anhydrous ethanol, and dry it in vacuo.
[0043] Example 2
[0044] A POSS-based compatibilizing component is prepared by the following steps:
[0045] 2.1 g of epoxidized vinyl POSS, 2.5 g of mercapto Schiff base, 0.02 g of benzoin dimethyl ether and 100 mL of tetrahydrofuran were added into a flask, stirred for 40 min, and then placed under an ultraviolet lamp (power 600 W, wavelength 365 nm) for reaction for 30 min, and the tetrahydrofuran was removed by rotary evaporation.
[0046] Epoxidized vinyl POSS is made by the following steps:
[0047] Add 110 mL of chloroform into a flask, and add 6 g of octavinyl-POSS, 25 mL of acetic acid and 0.8 mL of 98 wt % concentrated sulfuric acid in sequence, stir and heat to 60 ° C, add 50 mL of 30 wt % hydrogen peroxide solution into the flask, after the addition is complete, heat to reflux for 18 hours, after the reaction is completed, remove the upper liquid by separation, and wash the lower liquid with 8 wt % sodium bicarbonate solution and deionized water for 5 times respectively to remove the aqueous phase. The obtained solution is evaporated in a ventilated place at room temperature for 12 hours, and then vacuum evaporated at 60 ° C for 12 hours.
[0048] Mercapto Schiff bases are prepared by the following steps:
[0049] Add 0.1 mol cinnamaldehyde into a flask with 150 mL of anhydrous ethanol, stir for 5 min, then add dropwise a solution consisting of 0.1 mol β-mercaptoethylamine and 80 mL of anhydrous ethanol, and control the dropping rate to 4 mL / min. After the addition is completed, add acetic acid in an amount of 0.4 times the sum of the mass of cinnamaldehyde and β-mercaptoethylamine. Stir and react at 65 °C for 4 h. After the reaction is completed, cool to room temperature, remove anhydrous ethanol by rotary evaporation to obtain a crude product, recrystallize the crude product with anhydrous ethanol, and dry it in vacuo.
[0050] Comparative Example 1
[0051] This comparative example is octa-epoxy POSS, and the specific preparation method refers to step (1) in specific implementation example 1 in patent publication number CN116333321 B.
[0052] Example 3
[0053] A food packaging bag comprises the following raw materials in parts by weight: 28 parts of polylactic acid, 2 parts of poly(butylene 2,5-furandicarboxylate), 2 parts of the POSS-based compatibilizing component of Example 1, and 0.6 parts of modified zero-valent nano-iron.
[0054] The modified zero-valent nano-iron is prepared by the following steps:
[0055] Mix 28 mL of 1 g / L polyethylene glycol-400 aqueous solution with 100 mL of 1 mol / L ferrous sulfate solution, and add 100 mL of 2.5 mol / L potassium borohydride solution under nitrogen environment, stirring while adding. After the addition is completed, stir and react for 10 minutes, then use a 0.22 μm water-based microporous filter membrane, wash the filter cake with deionized water and then dry it, transfer it to anhydrous ethanol and stir it for 5 minutes, use a 0.22 μm water-based microporous filter membrane again, wash the filter cake with anhydrous ethanol and acetone twice respectively, and dry it again.
[0056] The method for preparing the above-mentioned food packaging bag comprises the following steps:
[0057] Polylactic acid and poly (butylene 2,5-furandicarboxylate) were dried in an oven at 80°C for 12 hours respectively, and then added into a mixer together with a POSS-based compatibilizer component and modified zero-valent nano-iron at a speed of 50 r / min and stirred for 30 minutes to obtain a mixture, which was transferred to a screw extruder and melt-extruded to obtain composite pellets. The composite pellets were made into food packaging film by a casting method, and then cut and processed to obtain food packaging bags.
[0058] The screw extruder is a twin-screw extruder. From the feed part to the head part, the temperatures of the seven zones are set to 170°C, 180°C, 190°C, 190°C, 190°C, 180°C, and 180°C respectively. The feed rate is 150g / min and the screw speed is 60r / min.
[0059] The extrusion section temperature of the casting equipment was 170°C, the die temperature was 230°C, and the cooling roller temperature was 25°C.
[0060] Example 4
[0061] A food packaging bag comprises the following raw materials in parts by weight: 25 parts of polylactic acid, 7 parts of poly(2,5-butylene furandicarboxylate), 3.5 parts of the POSS-based compatibilizing component of Example 1, and 0.8 parts of modified zero-valent nano-iron.
[0062] The modified zero-valent nano-iron is prepared by the following steps:
[0063] Mix 56 mL of 1 g / L polyethylene glycol-400 aqueous solution with 100 mL of 1 mol / L ferrous sulfate solution, and add 100 mL of 2.5 mol / L potassium borohydride solution under nitrogen environment, stirring while adding. After the addition is completed, stir and react for 20 minutes, then use a 0.22 μm water-based microporous filter membrane, wash the filter cake with deionized water and then dry it, transfer it to anhydrous ethanol and stir it for 10 minutes, use a 0.22 μm water-based microporous filter membrane again, wash the filter cake with anhydrous ethanol and acetone for 3 times respectively, and dry it again.
[0064] The method for preparing a food packaging bag is the same as that of Example 3, except that the extrusion section temperature of the casting equipment is 200° C., the die temperature is 230° C., and the cooling roller temperature is 30° C. The remaining steps and parameters are the same as those of Example 3.
[0065] Example 5
[0066] A food packaging bag comprises the following raw materials in parts by weight: 38 parts of polylactic acid, 12 parts of polybutylene 2,5-furandicarboxylate, 5 parts of the POSS-based compatibilizing component of Example 1, and 1.2 parts of modified zero-valent nano-iron.
[0067] The preparation process of modified zero-valent nano-iron is the same as that in Example 3.
[0068] The method for preparing a food packaging bag is the same as that of Example 3, except that the extrusion section temperature of the casting equipment is 230° C., the die temperature is 230° C., and the cooling roller temperature is 35° C. The remaining steps and parameters are the same as those of Example 3.
[0069] Comparative Example 2
[0070] A food packaging bag is prepared based on Example 3, wherein the POSS-based compatibilizing component in Example 3 is replaced by the octa-epoxy POSS in Comparative Example 1, and the remaining raw materials and preparation process are the same as those in Example 3.
[0071] Comparative Example 3
[0072] A food packaging bag is prepared based on Example 3, except that the modified zero-valent nano-iron in Example 3 is removed, and the remaining raw materials and preparation process are the same as those in Example 3.
[0073] The food packaging films obtained from Examples 3 to 5 and Comparative Examples 2 to 3 were tested, and the testing process was as follows:
[0074] (1) Mechanical properties
[0075] Referring to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the mechanical properties of the composite film were determined using an electronic universal testing machine. The film thickness was measured first, and then a dumbbell cutter was used to prepare the sample. The sample size was a dumbbell-shaped strip of 50 mm × 9 mm, the narrow part width was 4 mm, and the gauge length was 17 mm. The test was conducted at room temperature with a tensile speed of 10 mm / min. Five parallel samples were measured for each group of samples, and the average value was taken.
[0076] (2) Gas barrier properties
[0077] Each group of sample films was cut into discs with a thickness of 70 microns and a diameter of 8.6 cm, and the oxygen permeability was measured according to the standard of GB / T1038.1-2022 "Test method for gas permeability of plastic products, films and sheets - Differential pressure method" to obtain the oxygen permeability (expressed as OT value, the smaller the OT value, the better);
[0078] For each group of samples, three parallel samples were measured and the average value was taken;
[0079] (3) Freshness preservation performance
[0080] Fresh-cut broccoli was packaged with the food packaging film prepared in the embodiment and the comparative example, sealed with an easy-tear paper tape, and stored at a constant temperature of 25° C. On the third and fifth days, the paper tape was torn off, and the broccoli samples were taken out for observation and scored according to the color and smell sensory evaluation table (Table 1), and the average of the scores of 5 people was taken as the sensory evaluation score;
[0081] The test results are shown in Table 2;
[0082] Table 1 Color and smell sensory evaluation table
[0083]
[0084] Table 2 Test results
[0085]
[0086] It can be seen from the data recorded in Table 2 that the mechanical properties, oxygen barrier properties and fresh-keeping properties of the packaging films prepared in Examples 3-5 are better than those in Comparative Examples 2-3. Specifically, it can be seen from the test results of Comparative Example 2 and Example 3 that the "POSS-based compatibilizing component" in the present invention is replaced by "octaepoxy POSS", the presence of numerous active epoxy groups and excessive cross-linking lead to a significant decrease in the elongation at break of the obtained packaging film, and the lack of preparing the mercapto Schiff base with cinnamaldehyde as the raw material causes a significant decrease in the fresh-keeping property. It can be seen from the test results of Comparative Example 3 and Example 3 that the lack of modified zero-valent nano-iron causes the mechanical properties, oxygen barrier properties and fresh-keeping properties of the packaging film to decrease to varying degrees.
[0087] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A food packaging bag, characterized in that: The method comprises the following raw materials in parts by weight: 28-38 parts of polylactic acid, 2-12 parts of polybutylene 2,5-furandicarboxylate, 2-5 parts of POSS-based compatibilizing component, and 0.6-1.2 parts of modified zero-valent nano-iron; The POSS-based compatibilizing component is prepared by the following steps: Mix epoxidized vinyl POSS, mercapto Schiff base, benzoin dimethyl ether and tetrahydrofuran, stir for 20-40 minutes, place under ultraviolet light for reaction for 30 minutes, and remove tetrahydrofuran by rotary evaporation; The modified zero-valent nano-iron is prepared by the following steps: Mix the polyethylene glycol-400 aqueous solution and the ferrous sulfate solution, and add the potassium borohydride solution dropwise under a nitrogen environment while stirring. After the addition is complete, stir the reaction for 10-20 minutes, then filter, wash the filter cake and dry it.
2. A food packaging bag according to claim 1, characterized in that: The usage ratio of epoxidized vinyl POSS, mercapto Schiff base, benzoin dimethyl ether and tetrahydrofuran is 2-2.1 g: 2.5 g: 0.02 g: 50-100 mL.
3. A food packaging bag according to claim 1, characterized in that: Epoxidized vinyl POSS is made by the following steps: Octavinyl-POSS, acetic acid and concentrated sulfuric acid were added to chloroform in sequence, and hydrogen peroxide solution was added dropwise at 60°C. After the addition was completed, the temperature was raised to reflux for reaction for 18 hours, and the upper liquid was removed by separation. The lower liquid was washed with sodium bicarbonate solution and deionized water for 3-5 times respectively, and the aqueous phase was removed. The obtained solution was evaporated in a ventilated place at room temperature for 12 hours, and then vacuum evaporated at 60°C for 12 hours.
4. A food packaging bag according to claim 3, characterized in that: The usage ratio of chloroform, octavinyl-POSS, acetic acid, concentrated sulfuric acid and hydrogen peroxide solution is 110mL:6g:25mL:0.8mL:50mL, the mass fraction of concentrated sulfuric acid is 98%, and the mass fraction of hydrogen peroxide solution is 30%.
5. A food packaging bag according to claim 1, characterized in that: Mercapto Schiff bases are prepared by the following steps: Add cinnamaldehyde to anhydrous ethanol, stir and then drop an ethanol solution of β-mercaptoethylamine. After the addition is complete, add acetic acid and react at 55-65°C for 4 hours under stirring. Cool to room temperature and remove anhydrous ethanol by rotary evaporation to obtain a crude product. Recrystallize the crude product with anhydrous ethanol and dry it in vacuo.
6. A food packaging bag according to claim 5, characterized in that: The molar ratio of cinnamaldehyde to beta-mercaptoethylamine is 1:1, and the amount of acetic acid used is 0.2-0.4 times the sum of the masses of cinnamaldehyde and beta-mercaptoethylamine.
7. A food packaging bag according to claim 1, characterized in that: The mass concentration of polyethylene glycol-400 aqueous solution is 1 g / L, the concentration of ferrous sulfate solution is 1 mol / L, and the concentration of potassium borohydride solution is 2.5 mol / L.
8. The food packaging bag according to claim 1, characterized in that: The volume ratio of the polyethylene glycol-400 aqueous solution, the ferrous sulfate solution and the potassium borohydride solution is 28-56:100:
100.
9. A method for preparing a food packaging bag according to any one of claims 1 to 8, characterized in that: The following steps are involved: Polylactic acid and poly (butylene 2,5-furandicarboxylate) were dried in an oven at 80°C for 12 hours respectively, then added into a mixer together with a POSS-based compatibilizer component and modified zero-valent nano-iron, stirred for 30 minutes, transferred to a screw extruder, and melt-extruded to obtain composite pellets. The composite pellets were made into food packaging films by a casting method, and then cut and processed to obtain food packaging bags.
Citation Information
Cited By
Spice slow-release nanofiber membrane, preparation method and application
CN119308071A
